Al-Mawardi's Theory of State: Some Ignored Dimensions (American Journal of Islam and Society, 2001)
A manuscript of Al-Mawardi's important political work Tashilal-Nadar (Facilitating -Administration) has recently been published.Examining this work, it appears that beyond the stereotype, conformist,Abbasid-patronized writer, there is another Mawardi. Hence, anattempt is made in this article to show that some of Al-Mawardi's majorideas in political theory have not been seriously studied by any of themodem scholars who write on Islamic medieval political thought -most of whom have not even seen al-Mawardi's Tashil al-Nadar. I willargue, moreover, that what has been left out of al-Mawardi's works isprobably more relevant to political theory, and that some conclusionsarrived at in works that have become classics in the field are not wellfounded.